41 Solstice: sancuso in supportive and palliative care; a feasibility study in patients with cancer and refractory nausea and vomiting. Issue 3 (1st September 2017) - Villa, Shaun; Berman, Richard; Dean, Emma; Carter, Louise
Abstract : Background: Nausea and vomiting (N and V) are common, debilitating symptoms in patients with cancer, often precipitating inpatient admission for subcutaneous/intravenous antiemetics and re-hydration. Currently, there are no evidence-based solutions and treatment algorithms differ across clinical practice. Some of these patients will experience difficulty swallowing tablets and/or are unable to keep oral medications down. Treatments for patients with cancer may also reduce the ability of the intestines to absorb medicines within a tablet. SANCUSO (Granisetron Transdermal System [transdermal skin patch]) is indicated for the prevention of (N and V) in patients receiving moderately and/or highly emetogenic chemotherapy regimens. The SANCUSO patch delivers consistent, predictable levels of granisetron throughout five days with smoother daily pharmacokinetics compared to daily dosing. The role of Sancuso in patients with cancer and refractory N and V which is unrelated to chemotherapy has not yet been explored. Methods: An open-label, randomised feasibility study comparing SANCUSO with 'physician's choice' of antiemetic in patients with cancer and refractory N and V. A feasibility study is required at this juncture as standard antiemetic treatment in this patient population is undefined, and the therapeutic efficacy of SANCUSO requires appraisal before embarking on a larger randomised trial. To assess feasibility, we have categorised objectives into four domains; (i) Recruitment - assess the number of patients approached, consent rate, number of eligible patients and explore the methods used to identify potential patients (ii) Patients - willingness to participate and acceptability of the intervention (iii) Clinicians' - ability to recruit, which physician's choice is selected, experience including monitoring of prescribing practice in the control arm (iv) Trial procedures - determine the appropriate primary outcome, adherence/compliance rates. Implications: We aim to determine whether this approach is feasible and warrants further investigation in a larger randomised Phase II trial leading to a confirmatory multi-centre randomised Phase III trial to include a cost-effectiveness appraisal.